Approaches to migrant integration into local labor markets - Stryhul, Anton; Turlakova, Natalia (National Technical University "Kharkiv Polytechnic Institute", 2025)
This paper explores models of migrant integration into host country societies and labor markets. It argues that combining economic, social, and technological approaches can turn migration from a crisis trigger into an opportunity for sustainable growth. Case studies from Germany, Poland, and Canada illustrate effective practices in modern integration policy.
Keywords: integration; migration; labor market; migration policy